Factors Predicting Fly Density in Temporary Waste Shelters Bandung City - Agus Riyanto; Mona Megasari; Wulan Sriwahyuni (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Waste has become a problem in Bandung City and occupies rating second highest in West Java. Hoarding waste utilized vector flies for developing breeds. Height density fly describes the quality of the site environment the not good enough. The aim of this study is to assess factors that predict the density of flies on the spot in temporary shelter waste in Bandung City. Desain study is cross-sectional, sampling as many as 76 places of temporary shelter waste in Bandung City. Method data collection was used with interviews using questionnaires and observation of flies on the spot shelter waste using the fly grill. Analysis statistics use the chi-square test and examine big risk using the Prevalence Ratio (95% CI). Research results show that predicting factor fly density that is waste sorting (p= 0.002), waste collection (p= 0.0001), and waste transportation (p= 0.0001). Election waste is not good enough 1.5 times the risk of happening density fly high in place temporary shelter waste. Collection of waste is not enough good risk 1.9 times happen density fly high in temporary shelter waste. Freight waste is not enough good risk 2.3 times happen density fly high in place temporary shelter waste. The environment and hygiene Department may train officers on how to temporarily shelter waste about the method of handling trash, as well as give counseling to the Public to use appropriate in throwing away the trash. Abstrak: Sampah menjadi permasalahan di Kota Bandung dan menduduki peringkat kedua tertinggi di Jawa Barat. Penimbunan sampah dimanfaatkan vektor lalat untuk berkembang biak. Tingginya kepadatan lalat mengambarkan kualitas lingkungan di tempat tersebut kurang baik. Tujuan penelitian ini mengkaji faktor-faktor memprediksi kepadatan lalat di tempat penampungan sampah sementara di Kota Bandung. Rancangan penelitian ini potong lintang, sampel sebanyak 76 tempat penampungan sampah sementara Kota Bandung. Metode pengumpulan data dengan wawancara menggunakan kuesioner dan observasi lalat di tempat penampungan sampah menggunakan Fly grill. Analisis statistik menggunakan uji kai-kuadrat dan mengkaji besarnya risiko menggunakan Prevalens Ratio (95% CI). Hasil penelitian menunjukkan bahwa faktor yang memprediksi kepadatan lalat yaitu pemilahan sampah (p= 0.002), pengumpulan sampah (p= 0.0001), dan pengangkutan sampah (p= 0.0001). Pemilihan sampah kurang baik berisiko 1,5 kali terjadi kepadatan lalat tinggi di tempat penampungan sampah sementara. Pengumpulan sampah kurang baik berisiko 1,9 kali terjadi kepadatan lalat tinggi di tempat penampungan sampah sementara. Pengangkutan sampah kurang baik berisiko 2,3 kali terjadi kepadatan lalat tinggi di tempat penampungan sampah sementara. Dinas Lingkungan Hidup dan Kebersihan supaya memberikan pelatihan kepada petugas tempat penampungan sampah sementara tentang cara penanganan sampah, serta memberikan penyuluhan kepada masyarakat supaya tepat dalam membuang sampah.